Novel splice‐site mutation in ATP8B1 results in atypical Progressive Familial Intrahepatic Cholestasis Type 1. Issue 3 (26th February 2013) - Copeland, Emily; Renault, Nisa; Renault, Marc; Dyack, Sarah; Bulman, Dennis E; Bedard, Karen; Otley, Anthony; Magee, Fergall; Acott, Philip; Greer, Wenda L
Abstract Background and Aim Our objective was to identify the molecular genetic basis of an Alagille‐like condition not linked to JAG1 or NOTCH2 in two related sibships. Methods Because of common ancestry, and an autosomal recessive mode of inheritance, it was hypothesized that all affected and no unaffected individuals would be homozygous for the same haplotype in the region of the causative gene. Single nucleotide polymorphism arrays were therefore used to genotype 3 affected individuals from two sibships, their mothers and four unaffected siblings, to identify regions of homozygosity. Genes within the largest regions were prioritized and sequenced for mutations. Mutant RNA transcripts were also sequenced. Results A novel splice acceptor site mutation in the ATP8B1 gene was identified (a G–C preceding exon 16 resulting in a 4 bp deletion and frameshift from the 5′ end of exon 16). This result was unexpected because ATP8B1 mutations are associated with Progressive Familial Intrahepatic Cholestasis Type 1 (PFIC1). Intrahepatic bile duct paucity, cardiac anomalies, renal tubular acidosis and hypothyroidism led to an initial diagnosis of Alagille Syndrome. However, in retrospect, abnormal sweat chloride, normal gamma‐glutamyl transferase, normal to low cholesterol, and an autosomal recessive mode of inheritance were consistent with PFIC1. Renal tubular acidosis, hypothyroidism and cardiac anomalies have not previously been associated with PFIC1. Conclusion This work expands the phenotypic spectrum of PFIC1, and highlights the overlap in clinical phenotype between Alagille Syndrome and PFIC1. Knowledge of the causative mutation allows for carrier testing and prenatal diagnosis in this community.